The GIP receptor displays higher basal activity than the GLP-1 receptor but does not recruit GRK2 or arrestin3 effectively. - Suleiman Al-Sabah; Munya Al-Fulaij; Ghina Shaaban; Hanadi A Ahmed; Rosalind J Mann; Dan Donnelly; Moritz Bünemann; Cornelius Krasel (PLoS ONE)
Background and objectives Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are important regulators of insulin secretion, and their functional loss is an early characteristic of type 2 diabetes mellitus (T2DM). Pharmacological levels of GLP-1, but not GIP, can overcome this loss. GLP-1 and GIP exert their insulinotropic effects through their respective receptors expressed on pancreatic β-cells. Both the GLP-1 receptor (GLP-1R) and the GIP receptor (GIPR) are members of the secretin family of G protein-coupled receptors (GPCRs) and couple positively to adenylate cyclase. We compared the signalling properties of these two receptors to gain further insight into why GLP-1, but not GIP, remains insulinotropic in T2DM patients. Methods GLP-1R and GIPR were transiently expressed in HEK-293 cells, and basal and ligand-induced cAMP production were investigated using a cAMP-responsive luciferase reporter gene assay. Arrestin3 (Arr3) recruitment to the two receptors was investigated using enzyme fragment complementation, confocal microscopy and fluorescence resonance energy transfer (FRET). Results GIPR displayed significantly higher (P<0.05) ligand-independent activity than GLP-1R. Arr3 displayed a robust translocation to agonist-stimulated GLP-1R but not to GIPR. These observations were confirmed in FRET experiments, in which GLP-1 stimulated the recruitment of both GPCR kinase 2 (GRK2) and Arr3 to GLP-1R. These interactions were not reversed upon agonist washout. In contrast, GIP did not stimulate recruitment of either GRK2 or Arr3 to its receptor. Interestingly, arrestin remained at the plasma membrane even after prolonged (30 min) stimulation with GLP-1. Although the GLP-1R/arrestin interaction could not be reversed by agonist washout, GLP-1R and arrestin did not co-internalise, suggesting that GLP-1R is a class A receptor with regard to arrestin binding. Conclusions GIPR displays higher basal activity than GLP-1R but does not effectively recruit GRK2 or Arr3.